The effect of hydrolysis on combustion characteristics of sewage sludge and leaching behavior of heavy metals. Issue 20 (18th October 2018) - Ali, Mujahid; Huang, Qunxing; Lin, Bingcheng; Hu, Binhang; Wang, Fei; Chi, Yong
ABSTRACT: The aim of this paper is to present the effect of hydrolysis treatment on the thermal reaction characteristics of sludge and the leaching test of heavy metals contained in the sludge. Raw and hydrolysis-treated sludge (at temperature of 200°C and pressure 0.4 MPa) samples were collected from local municipal sewage sludge treatment plant. Thermogravimetric analysis was carried out between 25°C and 900°C at the heating rate of 10°C/min and 20°C/min under incineration and pyrolysis atmospheres. The leaching behavior of toxic heavy metals in the sludge was studied along with ash composition. The heating rate significantly changed the thermogravimetric and differential thermogravimetric curve profiles for studied fuels under different atmospheres. After hydrolysis treatment, the heavy metals of hydrolysis-treated sludge becomes more stable. The leaching concentration of Cr, Mn, Cu and Pb in hydrolysis-treated sludge were greatly reduced, when compared to raw sludge; however, no significant change was observed in Cd concentration. The X-ray diffraction pattern of bottom ash of hydrolysis-treated sludge was significantly reduced than raw sludge. This decrease is due to possible reduction in grain growth, which degrades the crystallinity of hydrolyzed sludge, implying that the hydrolysis treatment of sewage sludge could be a promising and beneficially safe disposal technology.